Strategic Planning Activity On Institutional Performance Through Knowledge Management And Training In The Office Of The Minister Of State And The Governor Of Dhofar - Musallam Ajaham Musallam Alkathiri; Khatijah Binti Othman; Muhammad Khairi Mahyuddin (OCERINT International, 2024)
Volume :5 Issue :14